Anks1a regulates COPII-mediated anterograde transport of receptor tyrosine kinases critical for tumorigenesis - Haeryung Lee (Nature Portfolio, 2016)
EphA2/ErbB2 complex is important in promoting breast cancer but the mechanism by which these receptor tyrosine kinases are exported from the endoplasmic reticulum is unknown. Here the authors show that Anks1a acts as a cargo adaptor in sorting EphA2 into COPII vesicles, thus modulating the surface level of EphA2.